(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The Author analyses the post mortem fertilisation treatments, which are forbidden by the l. no. 40/2004. Since the legal framework was provided in 2004, the jurisprudence has started an erosive interpretation of the law. However, the jurisprudence focuses only on one of the post mortem treatments. For such reasons, the Author analyses the new law on post mortem donation for research, l. no. 10/2020, in order to verify the compatibility of the new rules on reproductive cells and spare embryos.